2012
DOI: 10.1027/1614-0001/a000074
|View full text |Cite
|
Sign up to set email alerts
|

Temperamental Traits and Severity of PTSD Symptoms

Abstract: The paper presents the results of a longitudinal study of two groups of participants of motor vehicle accidents (MVA). They were investigated twice: The first time after 1–6 months (N = 362) or 12–24 months (N = 337) after a MVA, and then 1 year after the initial assessment. We assumed that, among the environmental variables (severity of experienced trauma, trauma-related prolonged stressors, other traumatic event and social support), two temperamental traits, emotional reactivity and briskness, would be facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 19 publications
1
16
0
6
Order By: Relevance
“…The results of our earlier studies [22,23,25] suggested that tendency for strong emotional reactions fosters development of trauma symptoms. Therefore, we expected that emotional reactivity, as the trait associated with neuroticism is important for increasing trauma symptoms, not only in clinical groups (cancer patients or HIV+ people) but also in professional groups.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The results of our earlier studies [22,23,25] suggested that tendency for strong emotional reactions fosters development of trauma symptoms. Therefore, we expected that emotional reactivity, as the trait associated with neuroticism is important for increasing trauma symptoms, not only in clinical groups (cancer patients or HIV+ people) but also in professional groups.…”
Section: Discussionmentioning
confidence: 84%
“…Both traits, ER and PE, were also positively correlated with somatic anxiety in students [24]. Emotional reactivity was also positively correlated, whereas BR was negatively correlated, with trauma symptoms in motor vehicle accident survivors [25]. Three other temperament traits i.e., BR, EN and AC are usually negatively correlated with the severity of trauma symptoms and likely act as resources that protect individuals against the risk of PTSD (the role of SS is unclear).…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of these studies suggest that high Briskness and Endurance may have positive effects on well-being. The beneficial role of Briskness was demonstrated in studies on stress (Fruehstorfer, Veronie, Cremeans-Smith, & Newberry, 2012;Zawadzki & Popiel, 2012) and the beneficial role of Endurance in studies on burnout (Cieslak, Korczynska, Strelau, & Kaczmarek, 2008).…”
Section: Beneficial Functions Of Briskness Endurance and Activitymentioning
confidence: 99%
“…Briskness is associated with less long-term PTSD (Zawadzki and Popiel 2012) and burnout symptoms (Rzeszutek and Schier 2014), similarly to endurance (Cieslak et al 2008). Activity is connected to a more advantageous mood profile (Jankowski and Zajenkowski 2012;Wytykowska 2012).…”
Section: Reported Effects Of Temperament Traits On Well-beingmentioning
confidence: 99%